Assessment of impact of fiscal policies in colombia (1964-1989) (1992)
This article examines the impact that the fiscal policy had on the economic activity based on a comparison between two subperiods: 1964-1974 and 1974-1989. Throughout the first period, the average GNP growth rate was higher than during the second periodo by analyzing both subperiods, a change in the orientation of  is evident: while in the first period the governments were in favor of intervention, during the second period they tend to a significant reduction in state intervention. The author concludes that in Colombia the fiscal policy which favors state intervention has been relatively successful.